2019
DOI: 10.3390/e22010009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fatigue Crack Growth Rate Based on Entropy Generation

Abstract: This paper presents the assessment of fatigue crack growth rate for dual-phase steel under spectrum loading based on entropy generation. According to the second law of thermodynamics, fatigue crack growth is related to entropy gain because of its irreversibility. In this work, the temperature evolution and crack length were simultaneously measured during fatigue crack growth tests until failure to ensure the validity of the assessment. Results indicated a significant correlation between fatigue crack growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
(75 reference statements)
0
6
0
3
Order By: Relevance
“…Sato et al reported that the fracture entropy generation of TriA-X polyimide was ~15.5 kJ/m 3 K [11]. Entropy-based damage evaluation has been experimentally confirmed for metallic [12][13][14], polymeric [9], and composite materials [15][16][17][18]. In the following, we distinguish between thermal and mechanical entropies.…”
Section: Introductionmentioning
confidence: 90%
“…Sato et al reported that the fracture entropy generation of TriA-X polyimide was ~15.5 kJ/m 3 K [11]. Entropy-based damage evaluation has been experimentally confirmed for metallic [12][13][14], polymeric [9], and composite materials [15][16][17][18]. In the following, we distinguish between thermal and mechanical entropies.…”
Section: Introductionmentioning
confidence: 90%
“…Recientemente, se han propuesto enfoques experimentales para evaluar la propagación de grietas [6,7], principalmente a partir del desarrollo de las técnicas modernas de medición de la temperatura, la cual, como se reporta ampliamente en la literatura [8][9][10][11][12], se puede correlacionar con la propagación de grieta por fatiga debido a que una gran variedad de estudios demuestran que, en la mayoría de los materiales metálicos, la energía de histéresis por deformación plástica se convierte en calor, como se reportó en el trabajo de Meneghetti et al [13].…”
Section: Antecedentesunclassified
“…Resultados de trabajos recientes demuestran que, a medida que crece la grieta, hay un aumento de la temperatura superficial de la probeta, lo cual plantea la necesidad de comprender los fenómenos físicos en la propagación de grietas por fatiga desde el punto de vista de la Termodinámica. Un ejemplo es el trabajo de Idris et al [19], quienes midieron simultáneamente la temperatura y la longitud de la grieta durante los Revista de Ciencias Tecnológicas (RECIT). Volumen 6 (1): 14-27 ensayos de crecimiento de grietas por fatiga hasta la ruptura, bajo condiciones de carga de amplitud constante y variable.…”
Section: Antecedentesunclassified
“…T m is the mean temperature, k is the thermal conductivity, a y is a parameter obtained by parabolic curve fitting to the temperature profile, ρ is the density, C is the heat capacity, h G is the global heat transfer coefficient, S conv is exchange surface, V spe is the specimen volume. Roslinda Idris et al [95] proposed an entropy-based model to predict the fatigue crack growth rate for dual-phase steel under spectrum loading. They monitored the crack length and temperature evolution during the fatigue crack test until failure to validate the estimation.…”
Section: Models Using Irreversible Entropy As a Metric With An Empiri...mentioning
confidence: 99%